Adaptive Flexible Sialylated Nanogels as Highly Potent Influenza A Virus Inhibitors. (30th June 2020) - Bhatia, Sumati; Hilsch, Malte; Cuellar‐Camacho, Jose Luis; Ludwig, Kai; Nie, Chuanxiong; Parshad, Badri; Wallert, Matthias; Block, Stephan; Lauster, Daniel; Böttcher, Christoph; Herrmann, Andreas; Haag, Rainer
Abstract: Flexible multivalent 3D nanosystems that can deform and adapt onto the virus surface via specific ligand–receptor multivalent interactions can efficiently block virus adhesion onto the cell. We here report on the synthesis of a 250 nm sized flexible sialylated nanogel that adapts onto the influenza A virus (IAV) surface via multivalent binding of its sialic acid (SA) residues with hemagglutinin spike proteins on the virus surface. We could demonstrate that the high flexibility of sialylated nanogel improves IAV inhibition by 400 times as compared to a rigid sialylated nanogel in the hemagglutination inhibition assay. The flexible sialylated nanogel efficiently inhibits the influenza A/X31 (H3N2) infection with IC50 values in low picomolar concentrations and also blocks the virus entry into MDCK‐II cells. Abstract : Fighting influenza : Through the combination of flexibility and multivalent binding, a sialylated nanogel is able to bind and adapt onto the influenza A virus surface. The resulting flexible nanogel efficiently blocks the virus binding onto the cell and inhibits infection at low pM concentrations.